Entrepreneurial competence development program: Implementing efficiency through knowledge sharing - Sergei Smirnov; Svetlana Dmitrichenkova; Elena Dolzhich; Gulnaz Murzagalina (Administrative Sciences, 2023)
The goal of this study was to investigate the impact of introducing methods used in other countries on student success. The results suggested that the introduction of specific practices to improve entrepreneurial competence would be more effective forgoing such special training methods. This was validated by the results of a test survey conducted by an expert panel. According to the panel, the quality of knowledge among students in the groups in which new methods were introduced was as follows: 7.5 points on average out of 10 for the first group; 7.9 points on average out of 10 for the second group; 7.8 points on average out of 10 for the third group; and 6.4 points on average out of 10 for the fourth group. These data suggest that new practices improve students' knowledge and skills. The students themselves also assessed the improvement in their quality of knowledge. More specifically, the students in the second group gave a very high average score of 4.4 out of a possible 5 for the effectiveness of the European methods. The same parameter was rated 3.4 out of 5 points by the fourth group.
Keywords: 350; economic activities; entrepreneurial competence; entrepreneurship; information exchange; knowledge transfer methods